A social network analysis of interorganisational collaboration: Efforts to improve social connectedness. (1st October 2022) - White, Kelsey B.; Resmondo, Zoë N.; Jennings, J'Aime C.; Creel, Liza M.; Kelly Pryor, Brandy N.
Abstract: The Covid‐19 pandemic has challenged public health practitioners and clinicians at multiple levels to intentionally consider the impact of social isolation on health outcomes. Many community‐based programmes design interventions to address tangible challenges within the social determinants of health, such as asset insecurity or food insecurity, to address health inequities. The growing need to address social isolation within marginalised communities also requires organisations to collaborate and create community partnerships that strengthen their own social integration within the community. The present research reports on the results of a Social Network Analysis (SNA) of community programmes within three southern U.S. cities and their local collaborations to address social isolation. After interviewing representatives of 46 community organisations, it was found that social service organisations that also offer public health services play a central role in community efforts to improve social isolation. The participating organisations primarily collaborate through referrals and information sharing, and report inadequate resources. With a growing recognition that social services and supports play a considerable role in addressing health inequities, this study provides evidence of opportunities for interorganisational collaboration to promote individual and community health.